Chatgpt Socialization in Increasing MSME Market Share in Rural Areas - Alan Rakhmat Putra; Nabila Cecilia Marasabesy; Damar Rais; Ratna Ayu Pawestri Kusuma Dewi; Hizkia Rikcanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service (PkM) activity aims to increase the market share and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) operating in rural areas through intensive socialization and training on the use of ChatGPT as an artificial intelligence (AI) tool . MSMEs in the focus area face digital marketing challenges that limit market reach. The PkM program was implemented for one week in the month of [Mention Month/Year of PkM] in three specific locations: Kersik Tuo Village (Kerinci, Jambi), which focuses on agribusiness; Untia Village (Makassar, South Sulawesi), which focuses on culinary and seafood; and Klampar Village (Pamekasan, Madura), which focuses on batik crafts. The methods used were hands -on training and individual mentoring. The PkM participants consisted of 90 MSMEs (30 participants from each village/sub-district) from the craft, culinary, and agribusiness sectors. The training materials included (a) a basic introduction to ChatGPT; (b) prompt engineering techniques for creating persuasive product descriptions and structured social media captions ; and (c) using ChatGPT as a simple market research assistant. Evaluation was conducted through measuring improvements in AI literacy (pre-test and post-test) and the resulting marketing content prototypes . The PkM results showed a significant increase in AI literacy (mean post-test score increased$35%$compared to the pre-test) and the participants' ability to create professional digital marketing content in a short time. After the training,$85%$Participants expressed optimism about immediately implementing ChatGPT in their daily marketing operations. The activity concluded that ChatGPT can serve as an effective digital equalization tool, reducing the technology access gap between urban and rural MSMEs, and directly increasing the potential market share of MSMEs in these villages.